Distribuição espacial da prevalência de aglutininas anti-lepitospira em bovinos em Cáceres, MT, Brasil 2005. - Suely Tocantins (2007)
The seroprevalence, distribution and space analysis of anti-leptospira agglutinins in cattle were studied in Sector I region, City of Cáceres-MT in 2005, using the empiric Bayesian statistic method for binomials data and scan statistics was utilized to evaluate possible areas of differential risk. A mapping was performed based on geographic letters of borders and divisions of pasture in 29 farms of the region. These properties owned a flock of cattle and their owners adhered to the study. A questionnaire was applied to obtain information regarded to the characteristics of the property, producer profile and reproductive and sanitary management. The sample size was 2.5% of cattle per occupied pasture based on a population, over four months, of 79,582 animals. 2123 samples of blood serum were collected from cattle among the following age groups 4 to 12 months, 13 to 24 months, 25 to 36 months and more than 36 months for both genders. The serums were tested by the microscopic agglutination technique for 17 leptospira serovars. An average of 15% of male and 85% of female serum reacted to at least one of the serum types totalizing 57.93% of all samples. The age groups presented significant differences among the results (p<0.001). The serovars hardjo (Hardjobovis) (30.88%), hardjo (Norma) (29.90%), hardjo (OMS) (18.81%) and wolffi (10.83%) were the most frequent. All the farms comprised serum reacted cattle and the mean prevalence of agglutinin anti-leptospira found in the 29 farms was 61.07%. The prevalence per pasture showed that the most affected age group was the one of 24 to 36 months (65.14%) followed by the age group of more than 36 months (63.34%). It was demonstrated, through the risk evaluation that, the infection by cattle pathogenic leptospira does not occur randomly, being two areas with a higher relative risk, a primary cluster with RR of 1.45 and a secondary one with RR of 1.38. The analyses have not revealed differences regarding to the animal management in the farms researched.